Firm Entry and Productivity Turnovers in Import Substituting Markets: Evidence from the Petrochemical Industry in Colombia - Luis H. Gutiérrez (Lecturas de Economía, 2005)
This paper analyses plant entry and productivity turnovers across Colombia's petrochemical industry for the 1974-1998 period. Results show that successful entrants shaped industry productivity and induced plant restructuring among incumbent plants. Entry flows increased steadily within plastics and boosted after trade liberalization. Total factor productivity growth decomposition shows that the incumbent effect dominates the turnover effect. Econometric results suggest that barriers to entry associated with plant technology licensing and dependence of imported raw materials deter entry while complementary market variables such as industry productivity levels, growth in housing construction, and fringe competition induce firm entry.